Impact of Open-Market Share Repurchases on Long-Term Stock Returns: Evidence From the Malaysian Market - Albaity, M.; Said, D.S. (SAGE Publications, 2016)
After the Asian financial crisis in 1997, firms listed on Bursa Malaysia were allowed to repurchase their shares on the open market. The number of companies engaged in share buyback is increasing and has become a tool to stabilize price by signaling undervaluation of the share. However, studies on share buyback in Malaysia are limited to the price performance surrounding the buyback events. This study aims to fill this gap by examining long-run price performance after the actual share buyback event over a sampling period of 2 years from 2009 to 2010 for Malaysian firms listed on FTSE Bursa Malaysia. There is no evidence to conclude that there exist long-term abnormal returns using the calendar-time portfolio approach that support the inefficient market hypothesis. On the contrary, buy-and-hold method was found to be significant supporting that the Malaysian stock market is semi-strong efficient.